2023
DOI: 10.1002/admi.202202296
|View full text |Cite
|
Sign up to set email alerts
|

Highly Reliable Electrochemical Metallization Threshold Switch Through Conductive Filament Engineering Using Two‐Dimensional PtSe2 Insertion Layer

Abstract: Electrochemical metallization threshold switch (ECM TS) has received significant attention for various applications owing to its high ON/OFF ratio, fast switching characteristics, and simple active electrode/dielectric layer/inert electrode structures. However, the excess diffusion of active metal ions causes severe variation in threshold voltage and poor endurance. Furthermore, the small room for inert electrode metal is a problem to be solved for various applications of ECM TS. Here, a novel structure is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This enables an atomically sharp transition between the two materials and essentially forbids Fermi level pinning. Such an interface is in contrast to conventional evaporated electrodes where the metal-induced gap states as well as defect-induced gap states deteriorate the contact properties and increase the carrier injection barrier. , Our TLM and device fitting estimates indicate that graphite electrodes provide a similar low contact resistance junction even with the thicker PtSe 2 devices due to a minor change in the work function of PtSe 2 with respect to the change in number of layers: an increase of approximately 10 meV for an increase in thickness from 2 to 5 nm. …”
Section: Electrical Characteristics For Fl Graphite-contacted Ptsementioning
confidence: 72%
“…This enables an atomically sharp transition between the two materials and essentially forbids Fermi level pinning. Such an interface is in contrast to conventional evaporated electrodes where the metal-induced gap states as well as defect-induced gap states deteriorate the contact properties and increase the carrier injection barrier. , Our TLM and device fitting estimates indicate that graphite electrodes provide a similar low contact resistance junction even with the thicker PtSe 2 devices due to a minor change in the work function of PtSe 2 with respect to the change in number of layers: an increase of approximately 10 meV for an increase in thickness from 2 to 5 nm. …”
Section: Electrical Characteristics For Fl Graphite-contacted Ptsementioning
confidence: 72%
“…Kumar et al 45 reported that vertically grown WS 2 , consisting of a ZnO layer-based memristor, exhibits a remarkable tunable dynamic range, accompanied by comprehensive synaptic functions. Kim et al 46 introduced an innovative approach by incorporating 2D platinum diselenide (PtSe 2 ) to engineer a thin and stable conductive filament; this resulted in high reliability, low-threshold voltage distribution (σ/μ ≈ 6.58%), and endurance (>10 6 cycles) in PtSe 2 -inserted ECM TS. Xue et al 47 introduced a multifunctional memristor featuring an Ag/combustion zinc oxide/W structure, demonstrating reliable digital resistive switching and biological synaptic behaviors like short/long-term plasticity.…”
mentioning
confidence: 99%